The Pessimistic Investor Sentiments Indicator in Social Networks - Rui Jin; Hong-Li Zhang; Xing Wang; Xiao-Meng Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
With the worldwide proliferation of social networks, the social networks have played an important role in the social activities .Peoples are inclined to obtain the corresponding public opinion to make decision such as shopping, education, investment and so on. Analysis of data generated by social networks has become an important field of research, however in the field of public opinion analysis of social networks the quantitative measure indexes are still lacking. In this paper, the calculation method of pessimistic investor sentiments indicator is proposed, and the index has a certain theoretical and practical value.